2007
DOI: 10.5123/s0101-59072007000100003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologia de pacientes co-infectados HIV/HCV atendidos na Fundação Santa Casa de Misericórdia do Pará

Abstract: Objetivo: descrever os aspectos epidemiológicos de pacientes co-infectados atendidos em um serviço de referência para hepatopatias, na cidade de Belém-PA. Método: realizou-se um estudo transversal de prevalência, utilizandose um protocolo de pesquisa contendo informações referentes à identificação e fatores de risco de 31 pacientes com sorologias positivas para o HIV e o HCV. Resultados: dez indivíduos (32,3%) receberam transfusão sangüínea; 20 (64,5%) eram heterossexuais; 18 (58,1%) referiram dois a cinco par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
6
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
3
6
0
2
Order By: Relevance
“…26 In the present study, the major risk factor found was sexual transmission, characterized by sexual promiscuity (84.3%), and STD acquisition (47.1%) between heterosexual patients. This is in accordance with the studies by Szwarcwald (2000) 27 and Amaral et al (2007), 4 who have also shown the predominance of coinfection among patients having heterosexual intercourse (68.6%) as compared with men having sex with men (MSM) (22.8%).…”
Section: Discussionsupporting
confidence: 79%
“…26 In the present study, the major risk factor found was sexual transmission, characterized by sexual promiscuity (84.3%), and STD acquisition (47.1%) between heterosexual patients. This is in accordance with the studies by Szwarcwald (2000) 27 and Amaral et al (2007), 4 who have also shown the predominance of coinfection among patients having heterosexual intercourse (68.6%) as compared with men having sex with men (MSM) (22.8%).…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, these aspects were associated with HIV-HCV coinfection in a univariate analysis. Likewise, other studies reported that these variables were risk factors of HIV-HCV coinfection 2 , 7 , 50 .…”
Section: Discussionmentioning
confidence: 86%
“…Among HIV/HBV coinfected individuals, the infection is more severe and causes more aggressive cases of cirrhosis and liver cancer. In this situation, the risk of cirrhosis increases 4.2-fold, mortality also increases, and, in some cases, the hepatitis B virus can be reactivated 8,9,10 .…”
Section: Introductionmentioning
confidence: 99%